(untitled) (REMUNOM, 2025)
This article addresses smoking as a serious global public health problem and highlights the essential role of nurses in addressing this challenge. Through health education strategies, therapeutic interventions, and psychological support, nurses play a crucial role in smoking cessation and in promoting a healthier society. In Brazil, public policies such as the National Tobacco Control Program have made progress in reducing tobacco consumption, but the role of nurses continues to be indispensable in implementing these measures, especially in individualized care and in leading support groups. The literature review shows that interventions led by nurses, such as motivational counseling and the use of nicotine replacement therapies, significantly increase cessation rates. Despite the advances, challenges such as work overload and the need for greater specific training persist, highlighting the importance of continued investment in training and resources.